Economic contribution, innovation and labour creation in batik industry - Mohamad Akhir, Noor Haslina (2017)
Batik is one of the handicraft products that belongs to the textile-based category. Batik refers to fabric-dyeing method with the resist technique. Starting with small-scale activities, the batik industry has since developed into a successful rural industry, which is also known at the national level. The Malaysian Handicraft Development Corporation acknowledges batik as the primary contributor to the sales of handicraft products in Malaysia. Despite its positive performance in the local market, some batik entrepreneurships are still regarded as microenterprises in terms of small and medium enterprise (SME) business classification. Hence, the firms are expected unable to reach their full potential or can only gain day-to-day income. This then raises a question in regards to the connection between the batik industry and the Malaysian economy. Therefore, the first issue is on measuring the economic contribution of the batik industry to the Malaysian economy. However, due to the limitation of series data related to batik industry performance, the Malaysian Input-Output Table 2010 will be used to measure the variables. Through the industrial linkage model, this study found that batik industry contributes significantly through the backward linkage, indicating a stimulating growth in terms of benefit from the batik industry to the other sectors rather than the batik industry alone. Furthermore, decomposition analysis results show that the first-order effect of injection in the private consumption of batik in final demand contributes to second and higher-order effects in the other sectors of the Malaysian economic structure. This is due to the additional input that is required to satisfy the increase in output demand. This study offers a new finding for the input-output theory related interindustry transactions between batik industry and other production sectors in the Malaysian context. The second issue highlighted in this study is related to the impact of innovation on batik firm performance. The evolution in the batik industry has led to innovation in the batikmaking process, batik products, marketing and organisational methods. However, some batik entrepreneurs follow traditional approach to manage their firm activities. Meanwhile, the third issue addressed in this study is about labour creation in the batik industry. Being a labour-oriented industry, batik entrepreneurs should have enough workers to manage each stage in the batik-making process and save the time, so that the number of production can be increased. However, at present, a majority of employees consist of older folks and contract workers (daily wage). Being a rural industry, batikmaking faces intense competition that may hinder its growth. In response to both issues, this study used data acquired from face-to-face survey in Kelantan and Terengganu to analyse the impact of innovation to the performance of batik industry and to determine which firm resources that influence labour creation in the batik industry. There are 62 batik firms in Kelantan and Terengganu that participated in this study. For the second objective, results from the ordinary least square method reveal that only product innovation has significant impact on batik firm performance. This study also offers a more detailed view on the effect of all four types of Schumpeterian innovation on batik firm performance. By using the same method, the third objective produces evidence for resource-based theory on labour creation. Results show that firm age and firm sales greatly influence labour creation in batik industry. The information about contribution, firm performance and labour creation in batik industry is important to help batik entrepreneurs to enhance the economic well-being of local communities in terms of job opportunities and household income. Overall, the batik industry is not only valuable to the development of Malaysian cultural heritage, but it is also an important asset to the country’s economic growth in the future, through its contribution as a successful rural industry.